Living Self-produced Digital Video as a Convenience for Experiential Learning in Fostering L2 Speaking Skill: A Study of Psycholinguistic from Vocational College Students View - Dian Heriani (Association of Language Teachers in Southeast Asia (ALTSA), 2022)
Learning a language is formed as a cognition process. Ideally, L2 learner engagement and speaking competence for college-level students build 21st-century communication that needs experiential learning. Meanwhile, college students (one academic semester) actively animate them in complex projects with real speaking experiences that indicate the novice L2 learner views speaking skills in the communication context. In addition, students perform reflective activities that revive them articulate the relevance and implications of the experience for continuing learning to link the academic, employability skills and knowledge they generate through these projects. To fill this study discloses a narrative case study that investigates how vocational college students (N=55) develop their experiential learning as a cognition process in learning English and learn 21st-century communication by self-produced video as novice L2 learners. Drawing on the contribution of psycholinguistics' perceptions (cognitive theory) and language exposure of students' experiential learning, focus on speaking skills through a video project. The study concluded that creating practical activities as experiential learning helps novice L2 learners successfully communicate and be aware of a cognitive area in learning English during online learning.